Design of Digital Economy Industry Investment Decision Support System Based on Fuzzy Comprehensive Evaluation Method - Shan, Xiaoyan (Informatica, 2024)
This study aims to explore the design and application of a digital economy industry investment decision support system based on fuzzy comprehensive evaluation method. With the rapid development of the digital economy, the complexity and uncertainty of investment decisions have increased significantly, and traditional decision-making methods are no longer able to meet the needs for efficient and accurate assessment. Therefore, this study constructs a comprehensive evaluation index system by introducing the fuzzy comprehensive evaluation method, aiming to provide a scientific and systematic decision-making tool for investors in the digital economy industry. The study first clarified the construction principles of the evaluation index system, including key indicators such as technological innovation capabilities, market potential, operational stability and risk control, and assigned corresponding weights. Then, by constructing a fuzzy relationship matrix and performing fuzzy comprehensive evaluation, a quantitative evaluation of different investment opportunities is achieved. The analysis results reveal the importance of technological innovation and market potential in investment decisions, while also emphasizing the need to comprehensively consider multiple evaluation indicators. This study further puts forward practical suggestions, including paying attention to technological innovation and market potential, balancing risks and rewards, continuously updating evaluation models to reflect the latest market and technology trends, and establishing an open information exchange and cooperation network. These suggestions are designed to help investors and decision-makers make more informed and forward-looking investment decisions in the digital economy industry.